PENERAPAN MODEL DISCOVERY LEARNING BERBANTUAN GEOGEBRA TERHADAP HASIL BELAJAR SISWA PADA MATERI BANGUN RUANG - Rahmi, Rahmi; Anwar, Anwar; Usman, Usman (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2024)
This research aims to determine the differences in student learning outcomes using the discovery learning model with and without GeoGebra assistance, which is motivated by the low ability to draw spatial figures. This research uses a quantitative approach with a pre and posttest control group design. The research sample was class VII-A students as the experimental class and class VII-B students as the control class, each with 20 students. The research was carried out at SMPN 1 Simpang Tiga Aceh Besar. Data collection was carried out using learning outcome test instruments that were given before (pretest) dan after (posttest) learning and had gone through a validation process. Research data was analyzed using the independent sample t-test. The results show the value of and or with a significance level of . So, it can be concluded that the learning outcomes of students who are taught using the discovery learning model assisted by GeoGebra are better than students who do not use GeoGebra in spatial construction material. This research can be developed on other geometric concepts.